2019
DOI: 10.1111/ecc.13086
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the prevalence of symptoms of depression, anxiety and distress in long‐term cancer survivors: Implications for primary care

Abstract: Introduction Symptoms of depression, anxiety and distress are common in the first years after a cancer diagnosis, but little is known about the prevalence of these symptoms at the long term. The aim of this review was to describe the prevalence of symptoms of depression, anxiety and distress in long‐term cancer survivors, five or more years after diagnosis, and to provide implications for primary care. Methods We performed a systematic literature search in the PubMed, PsycINFO and CINAHL databases. Studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 46 publications
4
76
1
Order By: Relevance
“…The previous meta-analyses of depression and anxiety in patients with cancers have shown that the overall estimates can be modified by several factors such as cancer types, time and method assessment of depression and anxiety, types (chemotherapy, radiotherapy, etc.) and time (pretreatment, on-treatment and post-treatment) of treatment, time from cancer diagnosis, consumption of time for assessment and status of disease (inpatients, outpatient, palliative care) [ 49 53 ]. For example, in a study by Walker et al [ 50 ], the pooled prevalence of depression in outpatients ranged from 5 to 16% while it was 7 to 49% in palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…The previous meta-analyses of depression and anxiety in patients with cancers have shown that the overall estimates can be modified by several factors such as cancer types, time and method assessment of depression and anxiety, types (chemotherapy, radiotherapy, etc.) and time (pretreatment, on-treatment and post-treatment) of treatment, time from cancer diagnosis, consumption of time for assessment and status of disease (inpatients, outpatient, palliative care) [ 49 53 ]. For example, in a study by Walker et al [ 50 ], the pooled prevalence of depression in outpatients ranged from 5 to 16% while it was 7 to 49% in palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…Defined as "diseases, conditions and syndromes that are continuing or occurring again and again for a long time […] and are justifiably emotionally and physically taxing for patients and their caregivers," [5] chronic health problems affect the health and well-being of many adults [1][2][3][4]. People living with chronic physical health problems are significantly more likely to experience psychological distress such as depression and anxiety [6][7][8][9][10] and lower quality of life [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This downward spiral is the result of an individual's coping response to their cancer experience, which is defined by the interaction between cancer stress and burden such as physical, financial, existential, and interpersonal burden and the resources available to that individual 5 . It is, therefore, not surprising that in the first year after cancer diagnosis, but also several years later, prevalence of depression, anxiety, and distress remain high, ranging between 5% and 50% for depression, 3% and 43% for anxiety, and 4% and 12% for distress 5,6 . As cancer survivors transition to primary care, general practitioners (GPs) resume their role as the first point of contact and will have a key role in the provision of psychosocial care for cancer survivors.…”
Section: Introductionmentioning
confidence: 99%